Analysis of Product Differentiation Through Problem Based Learning on the Level of Creativity of Class X Students of SMAN 2 Semarang - Solihah, Riyadhotus; Minarti, Ipah Budi; R, Rivanna Citraning; Mukaromah, Siti (Universitas Wiralodra, 2023)
The characteristics of students are different, so teachers need to accommodate this diversity to achieve the desired learning outcomes. One of the successes to be achieved in education is to create quality human resources by having creativity that is triggered by solving problems using problem-based learning models. The research objective was to measure the level of creativity of class X students of SMAN 2 Semarang after receiving learning with a differentiated learning method through problem based learning. The research was conducted in March 2023 at SMAN 2 Semarang, the research subjects were class X-4, which consisted of 36 students. This research is included in the quantitative descriptive method using various product assessment instruments or product differentiation, limiting the assessment of content assessment. The data analysis technique uses descriptive percentages to find out the categories of students' creativity levels. Based on the results of the data, it was found that the level of creativity of students who had the most frequency was Very High which consisted of 5 groups with scores of 94 and 100. This shows that problem-based learning with various presentation presentation products can increase student creativity.